Outlier Analysis of the Buchanan-three-phase Model used in fitting the Growth of Moraxella sp. B on Monobromoacetic acid (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2015)
Monohalogenated acetic acids have been widely used in industry and agriculture as precursor tochemicals and as herbicides, respectively. Monobromoacetic acid (MBA) is a chemicalintermediate for the manufacturing of various chemicals with application in agriculture andpharmacy. Bioremediation of monobromoacetic acid, has been touted as a more economical and feasible method compared to physical and chemical approaches. Previously, we model thegrowth of growth of Moraxella sp. B on monobromoacetic acid from published literature toobtain vital growth constants. We discovered that the Buchanan-three-phase model via nonlinear regression utilizing the least square method was the very best model to explain the growth curve. However, the use of statistical tests to choose the best model relies heavily on the residuals of the curve to be statistically robust. More often than not, the residuals must be tested for the presence of outliers (at 95 or 99% of confidence). In this work, the Grubbâ€™s test to detect the presence of outlier in the growth model was carried out.
Keywords: monobromoacetic acid-degrading, Buchanan-three-phase, Moraxella sp. B, ordinary least squares method, Grubbs test